2012
DOI: 10.1366/12-06636
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mercury (II) Ion Concentrations in Human Serum Albumin Using Fluorescence Spectroscopy and Multivariate Regression Analysis

Abstract: Human serum albumin (HSA) is a protein responsible for the transportation and delivery of drug molecules, fatty acids, and metabolites to various targets and the removal of waste products from the body. However, the binding of heavy metal ions, including mercury (II) (Hg(II)), can adversely affect HSA physiological properties with deleterious health consequences. The volatility of Hg at room temperature precludes the use of conventional flame, graphite furnace, or inductively couple atomic absorption spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Use of multivariate analyses, chemometrics, and data processing has also garnered considerable interest in biomedical, bioanalytical, biomedical, and clinical studies during this review period. For example, Fakayode’s research group has reported the first potential utility of fluorescence spectroscopy in conjunction with multivariate PLS regression analysis for accurate determination of Hg­(II) concentrations in human serum albumin (HSA) samples . Human serum albumin is a protein responsible for transport and delivery of drug molecules, fatty acids, and metabolites to various targets and removal of waste products from the body.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of multivariate analyses, chemometrics, and data processing has also garnered considerable interest in biomedical, bioanalytical, biomedical, and clinical studies during this review period. For example, Fakayode’s research group has reported the first potential utility of fluorescence spectroscopy in conjunction with multivariate PLS regression analysis for accurate determination of Hg­(II) concentrations in human serum albumin (HSA) samples . Human serum albumin is a protein responsible for transport and delivery of drug molecules, fatty acids, and metabolites to various targets and removal of waste products from the body.…”
Section: Data Analysesmentioning
confidence: 99%
“…For example, Fakayode's research group has reported the first potential utility of fluorescence spectroscopy in conjunction with multivariate PLS regression analysis for accurate determination of Hg(II) concentrations in human serum albumin (HSA) samples. 161 Human serum albumin is a protein responsible for transport and delivery of drug molecules, fatty acids, and metabolites to various targets and removal of waste products from the body. However, binding with heavy metal ions, including Hg(II), can adversely affect the physiological properties of has, with deleterious health consequences.…”
Section: ■ Data Analysesmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy has a large variety of important applications, including detection of illicit drugs, food safety testing, monitoring of environmental pollutants, medical diagnostics, and materials characterization, as well as airborne and spaceborne remote sensing of atmosphere components. 18 The most popular FT-IR spectroscopic instruments are tabletop instruments that are suitable for high-resolution spectroscopy measurements in laboratory, and the samples collected outside have to be sent to the laboratory for analysis, making the entire process time consuming. The tabletop FT-IR spectroscopic instruments that are large and have vibrational susceptibility are inapplicable for real-time on-site analysis.…”
Section: Introductionmentioning
confidence: 99%